Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M; Fagnano, M; Amoriello, T; Badiani, M; Ballarin-Denti, A; Buffoni, A; Bussotti, F; Castagna, A; Cieslik, S; Costantini, A; De Marco, A; Gerosa, G; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate - Manes, F; Vitale, M; Di Traglia, M (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract To investigate the real linkage and effectiveness of using the AOT40 index and ozone stomatal flux (FO3) in the assessment of physiological alteration/leaf injury on clover clones sensitive to ozone and Quercus ilex plants, two statistical techniques ? Partial Least Squares (PLS) and Neural Net Analysis (NNA) ? were applied. Different results were obtained in relation to the statistical method chosen. Linear methodologies applied to clover highlighted the role of temperature (TEMP) and O3 concentration (O3Mean) in affecting photosynthesis (PHOTO), leaf injury, and stomatal conductance (COND). In Quercus plants, COND was linearly correlated to two environmental variables, TEMP and Vapour Pressure Deficit (VPD), and to two physiological variables, PHOTO and Leaf Transpiration (TRASP), whereas PHOTO was correlated with TEMP, sO3, COND and sub-stomatal CO2/external CO2 ratio (Ci/Ca). These linear relationships were, in part, modified by NNA. In fact, non-linear relationships between environmental variables, and morphological and physiological variables were evident, suggesting caution when risk assessments are made on ozone concentration-based critical levels. Both plant types showed a relationship with FO3 that negatively affected leaf injury and PHOTO in clover and Quercus plants, respectively, suggesting that ozone flux-based critical levels were more effective in linking with leaf injuries or reduction in carbon metabolism.
doi: 10.1080/11263500500333966
Keywords: AOT40; Critical levels; Neural Net Analysis; Ozone; ozone stomatal ﬂux; PLS analysis